When Our Work Becomes Illegal: Navigating Anti-DEI Laws in Kentucky - Alexandra Howard; Courtney Shareef (The Political Librarian, 2025)
In 2025, Kentucky passed a law outlawing DEI offices, resources, and programming in public colleges and universities. In this article, we—two academic librarians at an urban, public research university in Kentucky—reflect on how that anti-DEI law renders much of our collaborative and individual work illegal. We provide a chronology of DEI-related changes over a five-year period at our institution, highlighting the shift from the university’s goal in 2020 of becoming a premier anti-racist research university to DEI now being outlawed at the university in 2025.
Keywords: DEI; anti-DEI; colleges; universities; academic libraries; inclusion